Military atlas of air warfare - Dougherty, Martin J. (Chartwell Books, 2014)
"The Military Atlas of Air Warfare" is a highly illustrated and accessible account of the development of aerial warfare, from the first skirmishes over the Western Front in World War I to today's hi-tech netcentric aerial battlespace.Developing from unpowered observation hot air balloons in the 18th century and even the older kite, aerial warfare has become a multibillion-dollar industry and has led to many advances in technology and techniques such as aerodynamics, propulsion, radar and use of composites and engineered materials such as carbon fibre. Featuring more than 120 complex computer-generated battle maps and graphics, "The Military Atlas of Air Warfare" explores every major air battle to have taken place in the world's skies, as well as documenting the air element of campaigns such as Operation Barbarossa and Operation Desert Storm. Extensively researched text tells the history and the stories behind these battles concisely and clearly.